Anticancer activity of oleiferoside B involving autophagy and apoptosis through increasing ROS release in MCF-7 cells and SMMC-7721 cells. Issue 22 (18th November 2021) - Feng, Suxiang; Zha, Zhengxia; Wang, Zhe; Yang, Ping; Wu, Jiangping; Li, Xia; Xu, Qiongming; Liu, Yanli
Abstract: Oleiferoside B is a triterpenoid monomer compound, mainly isolated from roots of Camellia oleifera Abel, the underlying mechanism of its antitumour is not clear. In the present study, oleiferoside B potently inhibited SMMC-7721 and MCF-7 cells proliferation and cause cells apoptosis. In addition, it activated an autophagy-mediated cell death pathway, as indicated by the accumulated the ratio of LC3- II/LC3- I and inhibited apoptosis protein expression after pre-treatment with autophagy inhibitors 3-MA. Further studies showed that oleiferoside B-induced apoptosis and autophagy was attributed to ROS release. In vivo oleiferoside B (1.0, 0.5 mg/kg) effectively suppressed tumour growth. In conclusion, our finding reveals a novel mechanism of action of oleiferoside B in cancer cells via induction of apoptosis and autophagy through ROS generation. Therefore, our results provided new insight into the mechanism of the antitumour effect of oleiferoside B as a prospective therapeutic drug in the tumour. Graphical Abstract: